The freshmen’s attitudes toward using videos in reading class - Ngo Nhat Phuong Quynh; Tran Thanh Phuong (Ho Chi Minh City Open University Journal of Science - Social Sciences, 2023)
Implementing video clips to enhance university students’ reading skills has been popular in Vietnam. This study aimed to explore the effects of employing video clips in reading improvement of English-majored freshmen from their perspectives. What is crucial here is whether applying video clips to teaching can boost the learners’ reading performance or not, as well as how profound their upgrade in reading is. For this study, the quantitative approach, as well as accumulating data, were applied to investigate the students’ perceptions regarding the cons that occurred when applying video clips to the development of their reading skills. To collect data for the study, fifty first-year English majors took part in the online questionnaire regarding their reading performance after the reading period through video clip assistance. The findings reflect that the majority of the students had a positive attitude toward utilizing videos in acquiring reading skills. As a result, with the implementation of videos in reading classes, students were motivated to engage in reading activities. Additionally, teachers are encouraged to make use of online video sources to increase the student’s motivation and engagement in acquiring reading skills.